Exploring potential mediating mechanisms between maladaptive perfectionism and athlete burnout based on multi-theory perspectives - Kang, Weiye; Gong, Chen (Frontiers in Psychology, 2024)
Background Athletes with maladaptive perfectionism are vulnerable to experiencing a variety of psychological issues, such as burnout. Burnout in athletes can have detrimental effects on their performance and careers. The potential mechanisms by which fear of failure and self-handicapping explain the association between maladaptive perfectionism and athlete burnout remain understudied. This study examined their mediating role in the relationship between maladaptive perfectionism and athlete burnout. Methods A total of 221 athletes were chosen to participate in a cross-sectional survey study. Data analysis was carried out using SPSS and AMOS structural equation modeling. The participants filled out self-report assessments on maladaptive perfectionism, fear of failure, self-handicapping, and athlete burnout. Results Analyses indicated that maladaptive perfectionism positively predicts fear of failure, self-handicapping, and athlete burnout. Fear of failure positively predicts self-handicapping and athlete burnout, while self-handicapping also predicts athlete burnout. In addition to the direct pathway, we identified three mediating pathways through mediation analyses: (a) an independent mediation of fear of failure (b) an independent mediation of self-handicapping (c) a chained mediation of both. Discussion The results of this study provide a better understanding of the underlying mechanisms between maladaptive perfectionism and athletes burnout by considering fear of failure and self-handicapping as mediating variable factors. It is shown that the relationship between maladaptive perfectionism and athlete burnout can be partially explained through the mediating role of individuals’ fear of failure as well as self-handicapping behaviors. These insights offer a valuable foundation for the design of psychological interventions to address athlete burnout, enabling coaches and sport psychologists to develop more effective coping strategies for enhancing athletes’ psychological well-being and performance.